The Effect of Current Ratio, Debt to Equity Ratio on Return On Assets Case Study of Pt.Tiga Pilar Sejahtera Food Tbk Period 2016-2024 - Dini Andiani; Rehan Febitri Rahmanda; Nurhana Dhea Parlina (Rescollacom (Research Collaborations Community), 2025)
PT Tiga Pilar Sejahtera Food Tbk (AISA) is facing financial challenges that affect its performance, including a decline in ROA. This study aims to investigate and assess the impact of the relationship between short-term liquidity ratio (CR) and debt to equity ratio (DER) on the rate of return on assets (ROA) at PT Tiga Pilar Sejahtera Food Tok from 2016 to 2024. The methodology in this research is a quantitative approach that applies various statistical analysis techniques, such as descriptive statistics, single linear regression, multiple linear regression, t-test, and F-test. The data source used in this research is the company's official financial documents, which are accessed through the website www.idx.co.id,i with an observation period of 9 years which resulted in 35 data. The main data source is the company's financial position report and income statement for the period. The results identified that CR has a considerable influence on ROA, while DER has no significant influence. When analyzed simultaneously, neither CR nor DER has a significant influence on ROA.